Wine Phenolic Compounds Differently Affect the Host-Killing Activity of Two Lytic Bacteriophages Infecting the Lactic Acid Bacterium Oenococcus oeni - Philippe, Cécile (Viruses, 2020)
To provide insights into phage-host interactions during winemaking, we assessed whether phenolic compounds modulate the phage predation of Oenococcus oeni. Centrifugal partition chromatography was used to fractionate the phenolic compounds of a model red wine. The ability of lytic oenophage OE33PA to kill its host was reduced in the presence of two collected fractions in which we identified five compounds. Three, namely, quercetin, myricetin and p-coumaric acid, significantly reduced the phage predation of O. oeni when provided as individual pure molecules, as also did other structurally related compounds such as cinnamic acid. Their presence was correlated with a reduced adsorption rate of phage OE33PA on its host. Strikingly, none of the identified compounds affected the killing activity of the distantly related lytic phage Vinitor162. OE33PA and Vinitor162 were shown to exhibit different entry mechanisms to penetrate into bacterial cells. We propose that ligand-receptor interactions that mediate phage adsorption to the cell surface are diverse in O. oeni and are subject to differential interference by phenolic compounds. Their presence did not induce any modifications in the cell surface as visualized by TEM. Interestingly, docking analyses suggest that quercetin and cinnamic acid may interact with the tail of OE33PA and compete with host recognition.